A Diagnostic Key to the Various forms of Introduced Mesquite (Prosopis juliflora Dc.) - Raizada, M. B.; Chatterji, R. N. (Indian Forester, 1954)
This paper contains a general account of the Mesquite - Prosopis glandulosa Torr. And P. julifiora DC., including the various forms of the latter. These trees were introduced into India as very promising species useful in afforesting dry and degraded lands. A historical review of their cultivation in India is included. Observations have also been made on their distribution and economic importance. Botanical descriptions of the genus Prosopis and its two species, mentioned above, are given. The behaviour of P. Juliflora as a composite species has been explained. The silvicultural characters and diagnostic features of the various forms of P. julifiora, including P. glandulosa, have been discussed and a key to their correct identification has been provided.